Life Skill Education Policy Implementation and Vocational Education Extracurricular Management and Its Impact on Student Independence - Dekawati, Ipong; Kurnaeti, Kokoy (Mimbar Ilmu, 2023)
One of the targets of graduates from educational institutions or schools is student independence. Especially for special schools, student independence is a necessity. Many factors can encourage student independence, including implementing life skills education policies and managing extracurricular vocational education. This research aims to analyze the magnitude of the impact of implementing life skills education policies and managing extracurricular vocational education on student independence. The method used in this research is a survey method with a quantitative approach, as well as correlational and regression techniques. Data collection techniques were through questionnaires with a Likert scale for 47 respondents. The results of data analysis show that first, there is a positive and significant influence of the implementation of life skills education policies on student independence. Second, there is a positive and considerable influence of extracurricular management of vocational education on student independence. Third, there is a positive and significant implementation of life skills education policies and the direction of extracurricular vocational education on student independence. To increase the effectiveness of managing extracurricular vocational education, it is recommended that school principals provide challenges with the hope that teachers will become more enthusiastic about working on extracurricular vocational education because there are exciting things to achieve. If the management of extracurricular programs is excellent, they will be included in achievement events, or their work will be patented.